Evaluasi Program Bantuan Stimulan Perumahan Swadaya (BSPS) di Kota Pagar Alam - Fadli, Muhammad; Prihatini, Lishapsari; Mardianto, Mardianto (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2021)
The purpose of this study was to analyze the success of the Self-help Housing Stimulant Assistance (BSPS) program in Pagar Alam City. The data analysis method used in this research is qualitative descriptive analysis. With data collection techniques from interviews, observations (observations in the field) and documentation studies. The informants of this research were information obtained from the Pagar Alam City Housing, Settlement and Land Office, the Pagar Alam City BSPS Consultant Team, and Aid Recipients in the 2019 BSPS Program intervention area.Regarding the results of the study as a special program targeting low-income communities, the BSPS program in Pagar Alam City can be said to be successful but not effective because there are still many people in low-income groups who have not been supported to achieve this, this is because the government's requirements directly burden beneficiaries because they should provide more funds or savings for construction and construction costs. With this BSPS program, it is hoped that it can improve the social life of the community with those who need assistance. Gotong royong, which has begun to fade, is expected to reappear through the presence of this program, although in the field only a few appear to be working together, others do not.Recommendations based on information obtained during this research, the amount of assistance becomes a burden for the beneficiaries, so it is necessary to consider whether the amount to be distributed will meet the needs of house construction or not. We need to increase the quota of recipients, because there are still many low-income people who do not own a house. Both use APBN and APBD funds. It is recommended that program activities financed by the APBN are accompanied by grants from the APBD to accelerate development and reduce problems and dilemmas in the community.